1986
DOI: 10.1099/0022-1317-67-2-289
|View full text |Cite
|
Sign up to set email alerts
|

An Epitope Located at the C Terminus of Isolated VP1 of Foot-and-Mouth Disease Virus Type O Induces Neutralizing Activity but Poor Protection

Abstract: SUMMARYBoth whole virus particles and isolated VP 1 of foot-and-mouth disease virus type O 1 induce neutralizing antibodies. Results obtained with pigs vaccinated with either isolated VP1 or intact particles and subsequently challenged show that neutralizing activity induced by intact virus correlates well with protection in pigs, whereas neutralizing activity induced by isolated VP1 confers little or no protection. Further evidence suggests that the epitope responsible for the induction of neutralizing antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Although the carboxyl terminus is not predicted to be a neutralizing site for Mengo virus, the analogous residues have been shown to contain or to potentiate the immunogenicity of a neutralizing epitope in two other viruses: FMDV (DiMarchi et al, 1986;Meloen & Barteling, 1986;Strohmaier et al, 1982;Thomas et al, 1988) and TMEV (Ohara et al, 1988). These viruses are both picornaviruses with TMEV being closely related to the cardioviruses, of which Mengo virus is a member.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the carboxyl terminus is not predicted to be a neutralizing site for Mengo virus, the analogous residues have been shown to contain or to potentiate the immunogenicity of a neutralizing epitope in two other viruses: FMDV (DiMarchi et al, 1986;Meloen & Barteling, 1986;Strohmaier et al, 1982;Thomas et al, 1988) and TMEV (Ohara et al, 1988). These viruses are both picornaviruses with TMEV being closely related to the cardioviruses, of which Mengo virus is a member.…”
Section: Discussionmentioning
confidence: 99%
“…In FMDV the C terminus peptide significantly increases the potency of residues 141 to 158 and may constitute an immunodominant antigenic domain (Parry et al, 1989) and be of importance in enhancing a protective response (Doel et al, 1988;Francis et al, 1985). Meloen & Barteling (1986) located what they term a minor 'neutralizing epitope' on the C-terminal end of isolated VP1 embracing residues 200 to 210 which induces neutralizing antibodies that correlate poorly with protection. This epitope may be related to the major neutralizing epitope, residues 141 to 158, as part of a discontinuous epitope (Meloen et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Early observations indicated that isolated VP1, and fragments derived from its carboxyterminal-half, were the only viral capsid products capable of inducing neutralising antibodies and conferring partial protection [12,134,163,229]. Thus, most attempts to develop synthetic vaccines were made using the entire VP1 or some of its fragments (reviewed in [38,39,49,79]).…”
Section: Proteins Protein Fragments and Viral Subunitsmentioning
confidence: 99%
“…Instead the FMDV ID gene of the two serotypes "O" and "A 22 " which encodes for major antigenic protein and induces immune response in animals (Meloen and Barteling 1986) was linked together and its expression was used to assess the transformation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The FMDV viral capsid consists of 60 copies of 4 structural proteins termed as VP1 (1D), VP2 (1B), VP3 (1C) and VP4 (1A). The immune-dominant epitopes are located on the 1D with in the G-H loop (140-160aa) and C terminal end (205-210aa) (Meloen and Barteling 1986). Thus ID gene has been exploited as the ideal candidate for development of edible vaccines (Carrillo et al 1998) for foot and mouth disease (FMD).…”
Section: Introductionmentioning
confidence: 99%